Northern Sea Cucumber (Cucumaria frondosa): A Potential Candidate for Functional Food, Nutraceutical, and Pharmaceutical Sector - Abul Hossain; Deepika Dave; Fereidoon Shahidi (Marine Drugs, 2020)
Sea cucumber (Cucumaria frondosa) is the most abundant and widely distributed species in the cold waters of North Atlantic Ocean. C. frondosa contains a wide range of bioactive compounds, mainly collagen, cerebrosides, glycosaminoglycan, chondroitin sulfate, saponins, phenols, and mucopolysaccharides, which demonstrate unique biological and pharmacological properties. In particular, the body wall of this marine invertebrate is the major edible part and contains most of the active constituents, mainly polysaccharides and collagen, which exhibit numerous biological activities, including anticancer, anti-hypertensive, anti-angiogenic, anti-inflammatory, antidiabetic, anti-coagulation, antimicrobial, antioxidation, and anti- osteoclastogenic properties. In particular, triterpene glycosides (frondoside A and other) are the most researched group of compounds due to their potential anticancer activity. This review summarizes the latest information on C. frondosa, mainly geographical distribution, landings specific to Canadian coastlines, processing, commercial products, trade market, bioactive compounds, and potential health benefits in the context of functional foods and nutraceuticals.